Analisis Regresi Ordinal Faktor-Faktor yang Mempengaruhi Capaian Literasi Matematika SMP dan SMA di Kabupaten Manggarai Barat - Patrisius Afrisno Udil; Dadan Dasari; Elah Nurlaelah (Department of Mathematics, Hasanuddin University, 2024)
This study aims to analyze the significant factors that affect mathematics literacy achievement, especially in junior and senior high schools in West Manggarai Regency. It begins by presenting descriptive information regarding mathematics literacy achievement at junior and senior high schools in West Manggarai Regency, especially in relation to other factors measured in the national assessment. This study is a quantitative study. The data analyzed were secondary data obtained from the Education, Youth and Sports Office of West Manggarai Regency in the form of Education Report. The analysis was carried out descriptively first, then analyzed with ordinal logistic regression. The results showed that the achievement of mathematics literacy at junior and senior high schools in West Manggarai Regency is still not optimal, both in general and in terms of each factor. The results of this study also show that the factors that significantly influence the achievement of mathematical literacy at junior and senior high schools in West Manggarai Regency include the level of the education unit, increased of learning quality score, increased of instructional leadership score, and increased of the algebraic content score.